Smart mechanosensing machineries enable migration of vascular smooth muscle cells in atherosclerosis‐relevant 3D matrices. (11th April 2017) - Chi, Qingjia; Shan, Jieling; Ding, Xiaorong; Yin, Tieying; Wang, Yazhou; Jia, Dongyu; Wang, Guixue
Abstract: At the early stage of atherosclerosis, neointima is formed due to the migration of vascular smooth muscle cells (VSMCs) from the media to the intima. VSMCs are surrounded by highly adhesive 3D matrices. They take specific strategies to cross various 3D matrices in the media, including heterogeneous collagen and mechanically strong basement membrane. Migration of VSMCs is potentially caused by biomechanical mechanism. Most in vitro studies focus on cell migration on 2D substrates in response to biochemical factors. How the cells move through 3D matrices under the action of mechanosensing machineries remains unexplored. In this review, we propose that several interesting tension‐dependent machineries act as "tractor"—posterior myosin II accumulation, and "wrecker"—anterior podosome maintaining, to power VSMCs ahead. VSMCs embedded in 3D matrices may accumulate a minor myosin II isoform, myosin IIB, at the cell rear. Anisotropic myosin IIB distribution creates cell rear, polarizes cell body, pushes the nucleus and reshapes the cell body, and cooperates with a uniformly distributed myosin IIA to propel the cell forward. On the other hand, matrix digestion by podosome further promote the migration when the matrix becomes denser. Actomyosin tension activates Src to induce podosome in soft 3D matrices and retain the podosome integrity to steadily digest the matrix.